Culture, time and publics in the Arab world media, public space and temporality - Sabry, Tarik 1969-; Khalil, Joe F. (London I.B. Tauris, 2019)
In this revealing new study, Tarik Sabry and Joe Khalil preside over an original new exploration of Arab culture. They employ subjects as varied as anthropology, media studies, philosophy, political economy and cultural studies to illuminate the relationship between culture, time and publics in an Arab context, whilst also laying the foundations for a much more nuanced picture of Arab society. The diverse themes and locations explored include communities at borders, in rural and urban locations, Syrian drama audiences, Egyptian, Saudi and Tunisian artists and activists and historical and contemporary Arab intellectuals. This fresh empirical research and interdisciplinary analysis illuminate intricate experiences that transcend local, national and religious boundaries and expose how Arab publics combine the media and technology to create a rich experience that shapes their collective imagination and social structure. Providing a grounded orientation to key debates on time and what can be defined as public in modern Arab cultures, Sabry and Khalil address teachers, students and those concerned about the delicate structures that underpin the upheavals of the modern Arab world.
ntroduction: Culture, Time and Publics in a Changing Arab Context, Tarik Sabry and Joe Khalil 1. Dis-Formations of Palestine, Helga Tawil-Souri 2. `OUR CHILDREN ARE A THREAT': Publics and the policing of cultural temporality in Egypt, Ramy M.K. Aly 3. Cultural Time and Everyday Life in the Middle Atlas Mountain Village of Ait Nuh, Tarik Sabry 4. Consuming the Past in Contemporary Beirut: The Case of Rawda Cafeduring Ramadan, Helena Nassif 5. Neo-Tajdeed? Rap in Saudi Arabia and Tunisia, Joe Khalil 6. Reflections on Time in Arabic Poetry, Atef Alshaer 7. Keywords in Arab Political Memory: Mahdi Amil's Vocabulary Revisited in 2017, Omar Al-Ghazzi 8. Rethinking Arab Philosophical Experience in the Time of Revolution, Abdelaziz Boumeshouli.
Includes bibliographical references and index.
Keywords: Civilization, Arab; Arab countries -- Social life and customs